A brief history of the Geological Survey of Israel. Issue 6 (26th March 2023) - Beyth, Michael
ABSTRACT: The Geological Survey of Israel (GSI) was founded in 1948 with the establishment of the State of Israel. Over the years, changes of the research directions were dictated by national needs as the population grew from less than 1 million to more than 9 million in 2020 in a small country of only 22, 000 km 2 with highly diverse geological features. This was associated with a change in the structure of the survey and establishing it as a key player in sustainable development and effective utilization of natural resources. It became possible by the upgrade of the staff levels and the research facilities after the survey was recognized as an independent research institute by the government. The achievement of the GSI as an applied science organization in response to the country's ever-developing challenges is going hand in hand with becoming an international geo-scientific recognized organization.